PEMANFAATAN GOOGLE FORM SEBAGAI ALAT EVALUASI PEMBELAJARAN PRAKTIS PAI - Muhammad Ridwan; Nur Azizah; Assadullah Arrauf; Arifmiboy Arifmiboy (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2024)
Evaluation activities are often problematic both in their effectiveness and efficiency. The learning evaluation activities that have occurred so far have provided clear evidence that in its implementation, teachers need a lot of money because they have to give question sheets to many students and it is also time-consuming to check.This study aims to examine the use of Google forms in helping the process of implementing learning evaluations today considering that the implementation of assessments using Google forms has been carried out in various schools.This article uses the literature review method (library research). The results show that the use of Google Forms as a learning evaluation media shows excellent potential in providing effective and efficient time in making questions. In addition, by using technology effectively, teachers can help students develop digital skills that are essential for success in this modern era..